Inoculum concentration and pathogenicity of Colletotrichum gloeosporioides in jatropha leaves (Jatropha curcas). - Paz-Lima, Milton Luiz da; Rietjens, Anderson Rodrigues; Silva, Franciele Cristina; Silva, Aline Suelen (Multi-Science Journal, 2018)
Abstract – In Brazil has been stimulated the use of Jatropha curcas as an alternative for use in biodiesel. Anthracnose-of-jatropha is a frequent disease main in regions and seasons with hot and moisture weather. The objective of this study was to evaluate the effect of inoculum concentrations and pathogenicity of C. gloeosporioides in jatropha leaves. Fruits and leaves collected during the rainy season (Urutaí, GO) presenting leaf spot symptoms were taken to the laboratory for isolation and identification of the pathogen. In light microscope he observed that this was an isolated Colletotrichum sp. From this isolate two assays were performed: a) inoculating test mycelial disks on potted plants (treatments with and without injury); b) conidial suspensions were inoculated at concentrations of 103, 104, 105 and 106 conídios.mL-1 using the method of "detached leaves" (wounding treatments with and without injury). In the first assay the plants showed a latent period of 11 days with an average severity of 1 %. In the second trial in treated wounds showed the highest values of area under the disease progress curve (AUDPC) for concentrations of 105 conídios.mL-1 (2938.2 + 178.5) and 106 conídios.mL-1 ( 3685.2 + 347.5), statistically different from the others. And in no injury treatments, dilution 104, 105 and 106 conídios.mL-1 statistically equal AACPD values differing only in minor inoculated concentration. Through this work we can see the pathogenicity of C. gloeosporioides in jatropha and point the concentration of 106 conídios.mL-1 as ideal for testing and resistance studies jatropha anthracnose.